Norvegų-lietuvių kalbų žodynas / Norsk-litauisk ordbok - Mickūnaitė Griškevičienė, Aurelija (Scandinavistica Vilnensis, 2018)
The dictionary is the first lexicographic work of this size devoted to the Norwegian and Lithuanian languages. It describes nearly 30,000 most common words and technical terms as well as relevant abbreviations. It also explains a number of untranslatable Norwegian concepts and contains abundant illustrations that allow not only to understand the meaning of Norwegian words, but also to get acquainted with their usage and stylistic connotations, as well as the principles of Norwegian grammar. Although the dictionary is primarily intended for Lithuanian users, there is some useful information about the Lithuanian accentuation and grammar for the speakers of the Scandinavian languages. Šiame pirmajame tokio dydžio norvegų ir lietuvių kalboms skirtame leksikografjos veikale aprašoma beveik 30 000 dažniausių ir aktualių dalykinių sričių žodžių, svarbių santrumpų, paaiškinamos neišverčiamos norvegiškos sąvokos. Straipsniuose gausiai pateikiama vartosenos iliustracijų, tad žodynas leidžia ne tik pažinti norvegų kalbos žodžių reikšmes, bet ir susipažinti su jos gramatika, stilistine žodžių verte. Nors žodynas pirmiausia skirtas lietuvių vartotojams, skandinavai jame taip pat ras naudingos informacijos apie lietuvių kalbos kirčiavimą ir gramatiką.